The students knowledge on the benefits of traditional medicine for health - Farihin Fadhilah Syarif; Shirly Gunawan (Institute of Computer Science (IOCS), 2023)
This research aims to recognize the knowledge level about the benefits of traditional medicine for health in students batch 2019, Faculty of Medicine, Tarumanagara University. This research is a descriptive study with a cross-sectional design of 106 students batch 2019, Faculty of Medicine, Tarumanagara University. The data was collected using validated questionnaires. The knowledge of students batch 2019, Faculty of Medicine, Tarumanagara University regarding self-medication is categorized into a good level of knowledge (76.41%), knowledge of traditional medicine and its classification in the category of sufficient knowledge (69.83%), as well as knowledge about natural ingredients and their benefits in the category of less knowledge (26.16%). The knowledge levels of students batch 2019 of the Faculty of Medicine, Tarumanagara University regarding the definition of traditional medicine and its classification is categorized as sufficient level of knowledge, and the level of knowledge regarding natural ingredients and their benefits is categorized as lack of knowledge.